ARAHAN PENGGUNAAN LAHAN DAN PERENCANAAN KONSERVASI TANAH DAN AIR DI DAS YEH EMPAS, TABANAN, BALI - I Gusti Agung Lanang Widyantara; I Nyoman Merit; I Wayan Sandi Adnyana (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2015)
Damage to forest resources has caused the environmental balance of watersheds (DAS) becomes damaged. It often causes the result of high levels of erosion. One of the land use changes that are currently happening is in Yeh Empas watershed. With this research can be known the proposed land use and appropriate land use planning on Yeh Empas watershed. Erosion prediction using the USLE (Universal Soil Loss Equation) method is to estimate how much the rate of erosion is happening and also to get an idea how good land management actions for the region. The proposed land use determination is using the scoring method by combining the slope factor of the field, the soil sensitivity of erosion, and the intensity of daily rainfall. Soil sampling was done by taking soil samples from a total of 11 samples of soil from the land unit. This research conducted to estimate the rate of erosion, to determines how much erosion can be tolerated in Yeh Empas watershed, and its relationship with the factors that influence it, as well as to determine the proposed of land use. The results of erosion prediction on each unit of land in the research area ranged from 1.75 to 1,254.96 tons/ha/year and has a grade level of erosion from slight to very severe. The result of tolerated erosion ranged from 15.06 to 24.32 tons/ha/year. The value of erosion prediction that exceeded from tolerated erosion value occurs on land units 7, 8, and 9. On that land units required proposed of land use and soil conservation techniques so that the value of erosion prediction could be below from tolerated erosion value. The analysis results of the proposed land use in Yeh Empas watershed, for areas inside the forest is proposed to protected forest (land units 1, 2, 3, 4, 5, and 6) and the management is by planting plants that are adapted to the contour lines of slope. In the areas outside the forest is proposed for annual crop cultivation area (land units 7, 8, and 9)the management with the farming plantation development, high density growing crops and terracing and also for crops cultivation area (land units 10 and 11) management by mulching, cover soil with high density and terracing.